1994
DOI: 10.1093/hmg/3.5.729
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of human polymorphic N-acetyltransferase: enzymatic analysis of 15 recombinant wild-type, mutant, and chimeric NAT2 allozymes

Abstract: Human polymorphic N-acetyltransferase (NAT2) catalyzes the N-acetylation of arylamine drugs and carcinogens. Human acetylator phenotype is regulated at the NAT2 locus and has been associated with differential risk to certain drug toxicities or cancer. We examined arylamine substrate and acetyl coenzyme A cofactor affinities, and the N-acetyltransferase catalytic activities of the wild-type and 14 different mutant or chimeric human NAT2 alleles expressed in an Escherichia coli JM105 expression system. NAT2 alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 0 publications
9
77
0
3
Order By: Relevance
“…NAT2 allozymes encoded by alleles with base substitutions at positions 191, 590, or 857 were found to be significantly more unstable in bacterial expression systems than the wild-type protein. 52,61,64 However, in these studies the amount of immunodetectable NAT2 protein was not different upon expression of the variant and wild-type alleles. This is in contrast to the earlier observations by Grant and coworkers 57 who showed that liver NAT2 content was markedly reduced in slow acetylators, suggesting that the artificial environment of bacterial expression systems may not accurately reflect what occurs in mammalian cells with regard to protein degradation.…”
Section: Human Natsmentioning
confidence: 56%
“…NAT2 allozymes encoded by alleles with base substitutions at positions 191, 590, or 857 were found to be significantly more unstable in bacterial expression systems than the wild-type protein. 52,61,64 However, in these studies the amount of immunodetectable NAT2 protein was not different upon expression of the variant and wild-type alleles. This is in contrast to the earlier observations by Grant and coworkers 57 who showed that liver NAT2 content was markedly reduced in slow acetylators, suggesting that the artificial environment of bacterial expression systems may not accurately reflect what occurs in mammalian cells with regard to protein degradation.…”
Section: Human Natsmentioning
confidence: 56%
“…NAT2-dependent N-acetylation ( Figure 1) and O-acetylation ( Figure 4) have been reported in urinary bladder cytosol from rapid and slow acetylator Syrian hamsters congenic at the NAT2 locus. As both NAT1 and NAT2 catalyse the metabolism of aromatic amine carcinogens (Minchin et al, 1992;Hein et al, 1993bHein et al, , 1994bHein et al, , 1995, genetic polymorphism in NAT1 and/or NAT2 may modify cancer risk related to exposures to these carcinogens.…”
Section: Phenotypic Expression Of the Nat2 Polymorphismmentioning
confidence: 99%
“…These two SNPs and identification of NAT2*12 and NAT2*13 alleles often are not determined in epidemiological studies as they are considered rare. However, as shown in Figure 5, their frequency is not rare in many ethnic groups and it is important both to assess their frequency and to correctly assign them as rapid or slow (Hein et al, 1994bFretland et al, 2001;Zang et al, 2005). Three studies using caffeine as a phenotype probe suggested that NAT2*12 and NAT2*13 were associated with slow acetylation phenotype (Cascorbi et al, 1995;Gross et al, 1999;Bolt et al, 2005).…”
Section: Molecular Basis For Altered Function Of Nat2 Polymorphic Varmentioning
confidence: 99%
See 1 more Smart Citation
“…After activation, HA are either detoxified or activated to more potent carcinogens by N-acetyltransferases (NAT1 and NAT2) [11]. Several polymorphisms are known in the NAT1 and NAT2 genes, which result phenotypically in individuals who are slow or rapid acetylators [12].…”
Section: Introductionmentioning
confidence: 99%